The saga of Sagamore. (4th December 2015) - Cooper, Malcolm
Abstract: The Sagamore series of triennial conferences, with their unique focus on electron charge, spin and momentum densities, has been in existence for over 50 years. Named after the location of the first two meetings, which were in the Adirondack hills of Upper New York state, the conferences are still held by and large in remote places with forests, lakes and mountains not far away and competing distractions not too near. They strive to maintain an accent on informal discussions sparked off by the keynote addresses. This article charts the history of the Sagamore series and the organisation behind them.